Evaluasi Kebijakan Pendidikan dalam Rangka Penguatan Kompetensi Guru Sekolah Dasar di Kabupaten Mamberamo Tengah: Kajian Berbasis Enam Kriteria William N. Dunn - Ameng, Bonavantura Gusto Nong Dion; Silo, Akbar; Sapioper, Hiskia C. M.; Tambaip, Beatus (Riviera Publishing, 2026)
The quality of basic education cannot be separated from the capacity and competence of teachers who are on duty at the forefront of learning. However, the reality on the ground shows that areas that are categorized as disadvantaged, frontier, and outermost (3T) areas, including Central Mamberamo Regency in Papua Mountainous Province, still face teacher competency problems that are far from being resolved. This study was conducted to evaluate education policies in an effort to strengthen the competence of elementary school teachers in Central Mamberamo Regency through the lens of six policy evaluation criteria proposed by William N. Dunn, namely effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The research design used is an evaluative case study with a descriptive qualitative approach. Data mining was carried out through in-depth interviews with 24 informants from seven stakeholder categories, observations in five schools, and document search, all of which were analyzed using the Miles and Huberman interactive model accompanied by triangulation of sources. The findings showed that of the total 254 teachers in 35 elementary schools, only 60.2% met the S-1 qualification and only 11.8% had an educator certificate, both well below the national average. When evaluated using all six Dunn criteria, the average score obtained was only 2.33 on a scale of 5, in the category of poor. The unavailability of electricity and internet access in almost all elementary schools turns out to play a role as a structural moderation variable that significantly weakens the effectiveness of various policy instruments that rely on the assumption of digital infrastructure. As a theoretical contribution, this study proposes three new propositions, namely the concept of policy design gap, educational deprivation cycle, and multi-stakeholder partnership ecosystem model as an alternative to education governance in 3T areas.